2011
DOI: 10.1080/13504509.2011.556814
|View full text |Cite
|
Sign up to set email alerts
|

Water shortages and countermeasures for sustainable utilisation in the context of climate change in the Yellow River Delta region, China

Abstract: With an increasing population and rapid development of the economy and society of the Yellow River Basin region, the Yellow River is at crisis point. The discrepancy between supply and demand of water resources is a key issue. In 2000-2006, the mean annual discharge of the Yellow River entering the delta was 13.2 billion m 3 , a reduction of 18.6 billion m 3 compared with the 1980s, and 9 billion m 3 less than in the 1990s. The water requirements of various sectors are increasing. Large amounts of water essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…According to Geist and Lambin [49] and Foley et al [14,50], agriculture is the largest contributor to tropical deforestation and is responsible for up to 35% of global greenhouse gas emissions, with demonstrated negative impacts on air and water quality, biodiversity, carbon sequestration and infectious disease transmission. On the other hand, it is shown that a more productive and resource-efficient agriculture can increase the availability of food and contribute to world food security, while at the same time preserving natural resources and biodiversity [51][52][53][54][55][56][57]. McDonald [58] also followed this finding and stressed that it is a universal observation, especially in developing and the least developed countries, indicating that hunger is widespread with many food production systems being unsustainable.…”
Section: Selected Aspects Of the World Hunger Problem: Around The Malthusian Theory And A Challenge To Feed The World Sustainablymentioning
confidence: 99%
“…According to Geist and Lambin [49] and Foley et al [14,50], agriculture is the largest contributor to tropical deforestation and is responsible for up to 35% of global greenhouse gas emissions, with demonstrated negative impacts on air and water quality, biodiversity, carbon sequestration and infectious disease transmission. On the other hand, it is shown that a more productive and resource-efficient agriculture can increase the availability of food and contribute to world food security, while at the same time preserving natural resources and biodiversity [51][52][53][54][55][56][57]. McDonald [58] also followed this finding and stressed that it is a universal observation, especially in developing and the least developed countries, indicating that hunger is widespread with many food production systems being unsustainable.…”
Section: Selected Aspects Of the World Hunger Problem: Around The Malthusian Theory And A Challenge To Feed The World Sustainablymentioning
confidence: 99%
“…As earlier discussed, land degradation is a serious issue in China, likewise other Asian countries as well. China is increasingly suffering from salinization throughout its arid regions as new irrigation oases are being developed and affects more than a fifth of land in China, particularly in Ningxia and Hetao irrigated plains along the Yellow River (Zhang et al, 2010a(Zhang et al, , 2011. Waterlogging and salinization affect between 2 and 3 million ha in India and Pakistan respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Airborne pollutants such as toxic heavy metals, ozone-forming chemicals, and releases of sulfur that contribute to acid rain will be reduced, which is one of the most serious pollutions in southwestern China. The ash and waste products from burning will, in most cases, be sufficiently benign to return to the soil (Zhang et al, 2002(Zhang et al, , 2011). There will be a considerable reduction in net carbon dioxide emissions that contribute to the greenhouse effect.…”
Section: Introductionmentioning
confidence: 99%
“…From 2004 to 2019, the proportion of per capita water resources in the YRB decreased from 40.2 to 37.9%. The shortage of water resources is increasingly serious in the YRB (Xu et al, 2005;Zhang et al, 2009;Ringler et al, 2010;Liu & Yang, 2012;Cai et al, 2017b), which is not conducive to the sustainable development of the ecological environment and society (Zhang et al, 2011). In this case, the State Council issued 'The Opinions on the Implementation of the Strictest Water Resources Management System' and 'The Assessment Method for the Implementation of the Strictest Water Resources Management System' in 2012 and 2013 and clearly proposed the red line of total water consumption for each region.…”
Section: Introductionmentioning
confidence: 99%